The Safety Illusion - Horvitz, Eric (Microsoft Research and Decision Education Foundation, 2014)
I hope that this presentation will help you to understand and master the safety illusion. My primary goal is to share insights with both new and experienced drivers about the surprising link between actions that seem safe when taken one at a time, and terrible surprises that you can expect will follow from repeated "safe" actions. The ideas run deeper than driving; they promise to help you to connect your decisions in the "now" with longer-term outcomes in your life. The insights about how rare events fuse together into high probability outcomes can help you to minimize costly unexpected surprises—and to raise the likelihood of achieving valuable outcomes that seem magical and serendipitous. Full mastery of the content makes use of some knowledge about probability, which you can learn from a mentor or via online materials. However, the key insights about the safety illusion (and it’s generalization, the single-action illusion) do not require probability. I hope you’ll make the investment in time and effort to understand the safety illusion, and then share the insights with your friends and family. They will likely find the ideas valuable and interesting—and perhaps surprising.